2020
DOI: 10.3390/foods9050662
|View full text |Cite|
|
Sign up to set email alerts
|

Fungistatic and Fungicidal Capacity of a Biosurfactant Extract Obtained from Corn Steep Water

Abstract: Biosurfactants are surface-active compounds that are produced by microorganisms, which in addition to their surfactant capacity, can possess interesting antimicrobial activities that are used in their incorporation into the agrifood industry. In this work, the preservative capacity of a novel biosurfactant extract obtained from a residual stream of the corn-milling industry was evaluated against two different fungi (Aspergillus brasiliensis and Candida albicans) under different biosurfactant concentrations (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…The biosurfactant extract obtained from CSL, after different steeping process, possesses a quite homogeneous composition. Regarding the capacity to reduce the surface tension, the biosurfactant extract obtained from CSL, in the current work, was able to reduce the surface tension of water up to 39.3 ± 0.5 mN/m with a CMC of 320.2 ± 12.9 mg/L which was also in consonance with the results obtained in previous works (López-Prieto et al, 2020, 2019b.…”
Section: Biosurfactant Extract Characterizationsupporting
confidence: 92%
“…The biosurfactant extract obtained from CSL, after different steeping process, possesses a quite homogeneous composition. Regarding the capacity to reduce the surface tension, the biosurfactant extract obtained from CSL, in the current work, was able to reduce the surface tension of water up to 39.3 ± 0.5 mN/m with a CMC of 320.2 ± 12.9 mg/L which was also in consonance with the results obtained in previous works (López-Prieto et al, 2020, 2019b.…”
Section: Biosurfactant Extract Characterizationsupporting
confidence: 92%
“…The big difference between fungicidal and fungistatic compounds lies in the fact that the first one is able to inhibit 99.9% of fungal growth, while the second has a lower inhibition (50%). Another definition also used is that fungicidal compounds are those that inhibit the regrowth (for many hours) of the pathogen after a limited exposure for a certain period of time, whereas fungistatic compounds would be those where, after its removal, a rapid new growth would be observed [ 64 , 65 ]. Thus, it can be said that this classification may be related to the amount/time of cell death permanence and not to the mechanism of the death cause.…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors concluded that the results obtained showed satisfactory antimicrobial effects of CSW on pathogenic fungi. 51 Copper oxychloride (Cu-Oxy) is a fungicide commonly used to control plant diseases. Fungicide formulations often feature chemical surfactants to optimize product efficiency.…”
Section: Lipopeptidesmentioning
confidence: 99%
“…On the other hand, C. albicans showed resistance to inhibiting growth. However, the authors concluded that the results obtained showed satisfactory antimicrobial effects of CSW on pathogenic fungi 51 …”
Section: Mannosylerythritol Lipids: Chemical Structures and Microbial...mentioning
confidence: 99%